2009
DOI: 10.17221/128/2009-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of lab-scale continuous alcohol-free beer production

Abstract: Lehnert R., Novák P., Macieira F., Kuřec M., Teixeira J.A., Branyik T. (2009): Optimisation of labscale continuous alcohol-free beer production. Czech J. Food Sci., 27: 267-275.In order to study the formation and conversion of the most important flavour compounds, the real wort used in alcohol-free beer fermentation was mimicked by a complex model medium containing glucose, yeast extract, and selected aldehydes. The fermentation experiments were carried out in a continuously operating gas-lift reactor with bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
(9 reference statements)
0
19
0
Order By: Relevance
“…The profile of quantified volatiles consisted of 5 alcohols (1-propanol, 2-methylpropanol, 2-methylbutanol, 3-methylbutanol and 2-phenylethanol) and 2 esters (ethyl acetate and isoamyl acetate). These compounds are considered as ones of the main alcohols and esters in beer Lehnert et al, 2009;Rodrigues, Caldeira, & Câmara, 2008;Willaert & Nedovic, 2006), the most abundant being ethyl acetate, isoamyl acetate, the amyl alcohols and isobutanol (Piddocke, Kreisz, Heldt-Hansen, Fog Nielsen, & Olsson, 2009). Also, these compounds are those currently analyzed by other authors because they are relevant flavor compounds in beer (Charry-Parra, DeJesús-Echevarria, & Perez, 2011;Kobayashi, Shimizu, & Shioya, 2008) and chosen as reference compounds when studying industrial processes for production of non-alcoholic beers (Catarino & Mendes, 2011;Mota et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The profile of quantified volatiles consisted of 5 alcohols (1-propanol, 2-methylpropanol, 2-methylbutanol, 3-methylbutanol and 2-phenylethanol) and 2 esters (ethyl acetate and isoamyl acetate). These compounds are considered as ones of the main alcohols and esters in beer Lehnert et al, 2009;Rodrigues, Caldeira, & Câmara, 2008;Willaert & Nedovic, 2006), the most abundant being ethyl acetate, isoamyl acetate, the amyl alcohols and isobutanol (Piddocke, Kreisz, Heldt-Hansen, Fog Nielsen, & Olsson, 2009). Also, these compounds are those currently analyzed by other authors because they are relevant flavor compounds in beer (Charry-Parra, DeJesús-Echevarria, & Perez, 2011;Kobayashi, Shimizu, & Shioya, 2008) and chosen as reference compounds when studying industrial processes for production of non-alcoholic beers (Catarino & Mendes, 2011;Mota et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The aroma profile is clearly damaged and other, less pleasant flavors, like bready, worty or caramel notes can appear Catarino et al, 2009;Lehnert et al, 2009;Sohrabvandi et al, 2010). To compensate these disadvantages many breweries use a modified brewing technology for the production of a more aromatic original beer.…”
Section: Introductionmentioning
confidence: 99%
“…High losses of volatile compounds have been reported during the lab-scale vacuum dealcoholization process and also when commercial regular beers and their related nonalcoholic beers were compared (Zürcher et al 2005;Montanari et al 2009;Lehnert et al 2009;Brányik et al 2012;Strejc et al 2013). In this study, the major losses were found over the initial period of the dealcoholization experiments, and, hence, although the system is only nearly comparable to the industrial scale ones, our results suggest that the volatile compound behavior is likely to be also comparable.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the major losses were found over the initial period of the dealcoholization experiments, and, hence, although the system is only nearly comparable to the industrial scale ones, our results suggest that the volatile compound behavior is likely to be also comparable. For this reason, we suggest that in thermal dealcoholization at industrial scale, some additional system to recover the aroma compounds should be implemented for further improvement of the organoleptic characteristics of the final product by adding them to it (Zürcher et al 2005;Lehnert et al 2009;Mota et al 2011). This could be achieved by separating the ethanol from the key compounds with processes such as pervaporation or by addition of appropriate amounts of the key flavor compounds to the final dealcoholized beer (Olmo et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the content of ethanol in beverages can be different in disparate countries and regions. In the Czech Republic, for example, the typical content of ethanol in beers is 3-4%, respectively 4-5% (beer strength 10°, respectively 12°) and 10 -13% v/v for wines [15][16][17][18] . Fermented alcoholic beverages are mainly produced using the yeast Saccharomyces cerevisiae, S. eubayanus and S. pastorianus (formerly S. carlsbergensis), but other yeasts such as Kluyveromyces sp.…”
Section: Production and Use Of The Alcoholsmentioning
confidence: 99%